A Strategy to Reduce the Waiting Time at the Outpatient Department of the National Hospital in Sri Lanka - Dilrukshi, P.A.D.; Nirmanamali, H.D.I.M.; Lanel, G.H.J.; Samarakoon, M.A.S.C. (International Journal o f Scientific and Research Publications, 2016)
Attached

The National Hospital o f Sri Lanka is a major healthcare service provider in the country. The hospital has been expanded with many healthcare facilities. The out-patient department (OPD) is the main division o f the hospital which provides their service to over two thousand patients daily. Queuing is a major challenge for healthcare services all over the world, particularly in the developing countries.
Keywords: OPD; patient; Queuing theory; service rate; waiting time